Adding protein to a carbohydrate pre-exercise beverage does not influence running performance and metabolism - Lopes, A. M.; Rios, M.; Beleza, J.; Carvalho, D. D.; Monteiro, S.; Montanha, T.; Martins, S.; Guimarães, J. T.; Fernandes, R. J.; Magalhães, J.; Teixeira, V. H.; Ascensão, A. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: To analyze whether pre-exercise CHO+PRO vs. CHO intake distinctly influences running performance and metabolic biomarkers along a various of exercise intensities. METHODS: In a randomized, double blind, counterbalanced, crossover and placebo control design, 10 middle distance runners were tested in 3 occasions. After 10 h of fasting, participants ingested isovolumic beverages (0.75+0.25g·BW-1 of CHO+PRO, 1.0g·BW-1 of CHO and placebo control) 30 min before a treadmill running incremental protocol of 4 min steps until exhaustion. Venous blood was collected at fasting, 30 min after beverage ingestion and after the 3rd and 7th running steps. Oxygen uptake-related variables, including respiratory exchange ratio, heart rate, plasma glucose, insulin, glucagon, free fatty acids, blood lactate concentrations, gastrointestinal discomfort and rate of perceived exertion were measured. RESULTS: The addition of PRO to CHO had no influence on the measured variables, which did not differ between conditions along all incremental protocol intensities. The intake of CHO+PRO (compared to CHO) tended to decrease glycemia (106.5±21.3 vs. 113.6±26.5) and to increase insulinemia (14.4±15.1 vs. 12.7±10.8) at intensities close to maximum oxygen uptake. CONCLUSIONS: The addition of PRO to a pre-exercise CHO beverage had no impact on running performance and related metabolic variables at a wide spectrum of exercise intensities.